Peran Pustakawan Referensi Perpustakaan UIN Imam Bonjol Padang dalam meningkatkan Literasi Informasi Mahasiswa - Ibnu Shiva, Ridho; Amini, Aisyah (UIN Imam Bonjol Padang, 2022)
The university library has an important role in supporting the teaching and research process as well as meeting the information needs of the academic community, especially students. Improving student information literacy is needed to help search and use information effectively and efficiently. Students' abilities related to information literacy will make it easier to write scientific papers and work on college assignments. The Reference Librarian has the role of helping users to find the information they need effectively and efficiently. The purpose of this study was to determine the extent of the role of reference librarians in improving Information Literacy for students. The method used in writing this article is a descriptive research method through a qualitative approach. Data collection techniques through interviews, observation and literature study. This study shows that reference librarians have played their role in improving Information Literacy, such as training and information literacy packages and various services to improve Information Literacy skills of UIN Imam Bonjol Padang students